Correlation between mother's knowledge and husband's support for the success of the Lactational Amenorrhea Method (LAM) - Wahyunnisa Indrarosiana; Ernawati Ernawati; Ivon Diah Wittiarika (Universitas Airlangga, 2021)
HIGHLIGHTS 1. Lactational Amenorrhea Method (LAM) is one of the natural contraception methods of postpartum women.2. Mothers' knowledge and husband's support for LAM contraceptive method was suggested to contribute to its success.3. Research and statistical instruments used found that the success of LAM contraceptive was related to mothers' knowledge, but not related to husband's support. ABSTRACTObjectives: This study aimed to analyze the relationship between mother's knowledge and husband's support for the success of LAM contraception in Brengkok Village, Brondong District, Lamongan Regency, East Java, Indonesia.Materials and Methods: This study was an analytic observational study with a sample of 46 mothers who gave exclusive breastfeeding to their babies who met the inclusion criteria. The research instrument used a questionnaire to determine the level of mother's knowledge and husband's support about exclusive breastfeeding. Spearman Rank Correlation Test was used for data analysis with a significance level of 0.05.Results: More than 50% of the respondents (25 respondents) successfully used the LAM method to prevent pregnancy. Statistical test showed that there was a relationship between mother's knowledge and success of LAM contraception with p value of 0.000, with a correlation coefficient of 0.523. Meanwhile, husband's support was not related to the success of LAM contraception with p value of 0.461 with a correlation coefficient of 0.111.Conclusion: Mother's knowledge is related to the success of LAM contraception, and there is no relationship between husband's support and the success of LAM contraception.